Computational Investigation of Bending Properties of RNA AUUCU, CCUG, CAG, and CUG Repeat Expansions Associated With Neuromuscular Disorders - Taghavi, Amirhossein; Yildirim, Ilyas (Frontiers in Molecular Biosciences, 2022)
Expansions of RNA AUUCU, CCUG, CAG and CUG repeats cause spinocerebellar ataxia type 10, Myotonic dystrophy type 2, Huntington’s disease, and Myotonic dystrophy type 1, respectively. By performing extensive molecular dynamics simulations, we have investigated the bending propensities and conformational landscapes adopted by 3×3, 2×2 and 1×1 internal loops observed in RNA AUUCU, CCUG, CAG and CUG repeat expansions using model systems having biologically relevant repeat sizes. We show that the conformational variability experienced by these loops are more complex than previous reports where a variety of unconventional hydrogen bonds are formed. At the global scale, strong bending propensity was observed in r(AUUCU)10, r(CCUG)15, r(CAG)20 and r(CUG)20 and, to a lesser extent, in r(AUUCU)4, r(CCUG)10, r (CAG)10 and r(CUG)10. Furthermore, RNA CAG repeats exhibit a tendency toward bent states with more than 50% of observed conformations having bending angles greater than 50°, while RNA CUG repeats display relatively linear-like conformations with extremely bent conformations accounting for less than 25% of the observed structures. Conformations experienced by RNA AUUCU repeats are a combination of strongly bent and kinked structures. The bent states in RNA CCUG repeats mostly fall into the moderately bent category with a marginal ensemble experiencing extreme bending. The general pattern observed in all the bent structures indicates the collapse of the major groove width as the mechanical trigger for bending, which is caused by alteration of base pair step parameters at multiple locations along the RNA due to local distortions at the loop sites. Overextension is also observed in all the RNA repeats that is attributed to widening of the major groove width as well as undertwisting phenomenon. This information and the rich structural repository could be applied for structure based small molecule design targeting disease causing RNAs. The bending propensities of these constructs, at the global level, could also have implications on how expanded RNA repeats interact with proteins.